Pentingnya Mengenalkan Pancasila dan Contoh Penerapan Nilai-Nilai Pancasila Sejak Anak Berusia Dini - Jenisa Tasya Kamila; Dinie Anggraeni Dewi (Civiliza Publishing, 2021)
The value of Pancasila is very suitable to be instilled in children because they are at an early age. So that when they grow up, they will adapt their behavior and attitudes to the values ​​of Pancasila. Children really need guidance to instill values ​​from others, especially Pancasila parents. This can be done through games, songs, entertainment and other fun ways for children. However, there is also a need to educate young children. The school makes education for the values ​​of Pancasila so that it can instill moral values ​​in its soul. Therefore, children can develop attitudes and actions based on the values ​​of Pancasila, making them develop into children with noble morals. In accordance with national expectations.